Application Of Traditional Engklek Games To Increase Mathematics Learning Outcomes For Class Iii Students 001 State Private School - Dona Selviana; Widia Islami; Rejeki Rejeki (STKIP Rokania Pasir Pangaraian, 2022)
There are still mathematics learning that uses conventional methods (lecture). Students are less actively involved during learning. There are several obstacles during the learning process, one of which is: 1. Some student divert it by playing with their seatmates and sometimes chatting during learning because students think mathematics is a difficul lesson to understand and remember the material being studied. 2. Lack of student activity in learning, students to be less active andrigid in the learning outcomes in mathematics, this research uses Classroom Action Research(PTK). The purpose of this Classroom Action Research is to determine the insrease in mathematics learning outcomes for thir grade students at SD Negeri 001 Rambah by using the Game Traditional Engklek. Whicth it can be seen from the aplication of the traditional Engklek game. From the results of the research cycle I and the results of the research cycle II showed an increase in the percentage and completeness. Conclusion This classroom action research is that the application of the traditional Engklek game can improve mathematics learning outcomes for third grade student of SD Negeri 001 Rambah.